2002
DOI: 10.1175/1520-0469(2002)059<1959:lseoma>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Longwave Scattering Effects of Mineral Aerosols

Abstract: Scattering in the longwave domain has been neglected in the first generation of radiative codes and is still neglected in most current GCMs. Scattering in the longwave domain does not play any significant role for clear-sky conditions but recent works have shown that it is not negligible for cloudy conditions. This paper highlights the importance of scattering by mineral aerosols in the longwave domain for a wide range of conditions commonly encountered during dust events. The authors show that neglecting scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 34 publications
(42 reference statements)
9
130
0
Order By: Relevance
“…Scattering of longwave radiation by mineral dust is neglected in our radiative calculations. As reported by Dufresne et al (2002), this may lead to an underestimation of longwave radiative forcing by up to 50% at TOA and 15% at the surface. It should be noted that dust optical properties are calculated in the longwave region (divided into 16 spectral bands) by using the work of Koepke et al (1997).…”
Section: Radiative Effect Parametrization and Dust Optical Propertiesmentioning
confidence: 82%
See 2 more Smart Citations
“…Scattering of longwave radiation by mineral dust is neglected in our radiative calculations. As reported by Dufresne et al (2002), this may lead to an underestimation of longwave radiative forcing by up to 50% at TOA and 15% at the surface. It should be noted that dust optical properties are calculated in the longwave region (divided into 16 spectral bands) by using the work of Koepke et al (1997).…”
Section: Radiative Effect Parametrization and Dust Optical Propertiesmentioning
confidence: 82%
“…Dufresne et al (2002) indicate also positive surface forcings comprised between +21 and +29 W/m 2 , for six different atmospheric profiles. Finally, three dimensional modelling have been performed by Yoshioka et al (2007), who reported a mean annual value of +14 W/m 2 over the North Africa region, by using the CCSM3 model.…”
Section: Infrared Spectral Rangementioning
confidence: 88%
See 1 more Smart Citation
“…Uncertainties in the dust LW absorption coefficient are probably responsible for this difference. It should be recalled here that the LW scattering effect of mineral dust is not taken into account in CNRM-RCSM4 (Dufresne et al 2002). Figure 10 presents the semi-direct aerosol effect, resulting from calculations achieved thanks to the C-NO simulations.…”
Section: à2mentioning
confidence: 99%
“…In spite of more robust climate predictions in the last years, radiative forcing (RF) induced by aerosols is still the largest uncertainty to the total RF estimate (IPCC, 2014). The vertical distribution and relative location are determining factors of aerosol radiative forcing in the long-wave spectral range (Dufresne et al, 2002;Kaufman et al, 2002).…”
mentioning
confidence: 99%